The Year of the Perfect Christmas Tree - Houston, Gloria (New York, 1988)
Ruthie and her mother wonder how they will fulfill their obligation of getting the perfect Christmas tree to the town for the holiday celebration, since Papa has left the Appalachain area to go to war.
Texas Bluebonnet Award 1991-92
Easy